ショウワキチ ノ カイヒョウチュウ ニ ミラレタ チャクショク ソウ ノ セイタイガク テキ カンサツ - 星合, 孝男; ホシアイ, タカオ; HOSHIAI, Takao (国立極地研究所, 1969)
P(論文) Ecological observations of the coloured layer in the sea ice were carried out at Syowa Station from March 1967 to January 1968 The results obtained are as follows 1 A brown layer was formed at the bottom of the new ice in March 1967 It remained till the early part of January 1968 2 The thickness of the coloured layer was 2 cm in March and grew to 20 cm by May The brown colour faded with the lapse of time The chlorophyll-a concentration was high in the coloured layer, especially in the deep-brown part The chlorophyll-a conccntiation increased between March and April, but thereafter it decreased gradually 3 Horizontal extent of the coloured layer was not very wide, being 50m × 150m 4 The vertical situation and the thickness of the coloured layer varied from place to place However, it was geneially recognized that chlorinity and pH value were high in the upper part of the coloured layer and decreased in the lower part 5 Seasonal variation of chlorinity in the coloured layer was relatively remarkable Chlorinity was high between October and December 6 Seasonal change of pH value in the coloured layer was more remarkable than in the colourless part Between the latter part of December and the caily part of January pH value was exuemely high 7 On the 24th ol December, another coloured layer appeared at the bottom of the sea ice, accompanied by some increase of chlorinity and pH It disappeared by the 5th of January. departmental bulletin paper